Optimization of rice syrup production by solid-state fermentation using Aspergillus tamarii - Chanthana Chanchomsuk; Kamonlak Wicharaew; Kanok-orn Srimuang; Trakul Prommajak; Ratana Attabhanyo; Trakul Prommajak; Ratana Attabhanyo (Songklanakarin Journal of Science and Technology (SJST))
This study aims to optimize the solid-state fermentation process for rice syrup production, focusing on the interplay between various fermentation parameters such as water-to-rice ratio, inoculum volume, and fermentation time. Quadratic models were employed to establish relationships between these independent variables and several response variables, including syrup volume, total soluble solids (TSS), and concentrations of reducing sugar, glucose, and maltose, as well as reducing sugar yield. The optimal conditions for maximizing these responses were determined to be a water-to-rice ratio of 3:1, an inoculum volume of 10 mL, and a fermentation time of 60 minutes. Validation of the models revealed a strong correlation between predicted and actual values for all response variables, confirming the models' robustness. Comparative analyses with traditional rice-based beverages, like amazake, showed that the reducing sugar and glucose concentrations achieved were competitive.